Rotator cuff calcific tendinopathy: from diagnosis to treatment - Chianca, Vito; Albano, Domenico; Messina, Carmelo; Midiri, Federico; Mauri, Giovanni; Aliprandi, Alberto; Catapano, Michele; Pescatori, Lorenzo Carlo; Monaco, Cristian Giuseppe; Gitto, Salvatore; Pisani Mainini, Anna; Corazza, Angelo; et al. (Acta Biomedica Atenei Parmensis, 2018)
Rotator cuff calcific tendinopathy (RCCT) is a very common condition caused by the presence of calcific deposits in the rotator cuff (RC) or in the subacromial-subdeltoid (SASD) bursa when calcification spreads around the tendons. The pathogenetic mechanism of RCCT is still unclear. It seems to be related to cell-mediated disease in which metaplastic transformation of tenocytes into chondrocytes induces calcification inside the tendon of the RC. RCCT is a frequent finding in the RC that may cause significant shoulder pain and disability. It can be easily diagnosed with imaging studies as conventional radiography (CR) or ultrasound (US). Conservative management of RCCT usually involves rest, physical therapy, and oral NSAIDs administration. Imaging-guided treatments are currently considered minimally-invasive, yet effective methods to treat RCCT with about 80% success rate. Surgery remains the most invasive treatment option in chronic cases that fail to improve with other less invasive approaches.